KUPU-KUPU (Rhopalocera) DI KAWASAN HUTAN KOTA BNI BANDA ACEH - Alfida Alfida; Ulia Hanum; Eliyanti Eliyanti (Universitas Islam Negeri Ar-Raniry, 2016)
A study on Butterflies (Rhopalocera) in the BNI forest park Banda Aceh, Tibang village Syiah Kuala subdistrict has been conducted on Mei 2014. The aim of this research was to know the species of butterflies (Rhepalocera) in that space. The data were gathered by using explorative survey method by using purposive sampling technique. They were analyzed by using descriptive qualitative. It was found that there were 18 species of Rhepalocera which were classified into 3 familia ((Nympalidae, Pieridae, dan Papillionidae) in one order. Among all familia found, Pieridae were the most dominant familia (50%) found in the forest with 9 species, while Nympalidae was 33.33% and papillionidae was 16.7%. The species that were cought the most were Dananus chrysippus L and Celastrinaladon sp. There were 16 species of butterflies were found the most in the third observation point, they were 6 species of Nympalidae, 7 species of Pieridae, dan 3 species of Papillionidea.